Ответ:
1) (3·x²-2·x)+(-х²+3·x)=3·x²-2·x-x²+3·x=3·x²-х²+3·x-2·x=2·x²+x;
2) (4·c²-2·c·d)-(-10·c²+8·c·d)=4·c²-2·c·d+10·c²-8·c·d=4·c²+10·c²-2·c·d-8·c·d=14·c²-10·c·d;
3) (12·m²-7·n-3·m·n)-(6·m·n-10·n+14·m²)=12·m²-7·n-3·m·n-6·m·n+10·n-14·m²=
=12·m²-14·m²-3·m·n-6·m·n+10·n-7·n=-2·m²-9·m·n+3·n;
4) (3·n³-2·m·n+4·m³)-(2·m·n+3·n³)=3·n³-2·m·n+4·m³-2·m·n-3·n³=
=3·n³-3·n³+4·m³-2·m·n-2·m·n=4·m³-4·m·n.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1) (3·x²-2·x)+(-х²+3·x)=3·x²-2·x-x²+3·x=3·x²-х²+3·x-2·x=2·x²+x;
2) (4·c²-2·c·d)-(-10·c²+8·c·d)=4·c²-2·c·d+10·c²-8·c·d=4·c²+10·c²-2·c·d-8·c·d=14·c²-10·c·d;
3) (12·m²-7·n-3·m·n)-(6·m·n-10·n+14·m²)=12·m²-7·n-3·m·n-6·m·n+10·n-14·m²=
=12·m²-14·m²-3·m·n-6·m·n+10·n-7·n=-2·m²-9·m·n+3·n;
4) (3·n³-2·m·n+4·m³)-(2·m·n+3·n³)=3·n³-2·m·n+4·m³-2·m·n-3·n³=
=3·n³-3·n³+4·m³-2·m·n-2·m·n=4·m³-4·m·n.